Developing and optimizing a biocompatible tauopathy model using extracellular vesicle-mediated gene delivery - Ghadami, Samaneh; Dellinger, Kristen (Frontiers in Medicine, 2025)
IntroductionTauopathy models are essential in vitro systems for investigating tau-targeted therapies and advancing Alzheimer’s disease research. Extracellular vesicles (EVs), owing to their high biocompatibility, low toxicity, and reduced immunogenicity, represent promising carriers for gene delivery and disease modeling.MethodsWe investigated the potential of EVs as a delivery system for the human four-repeat tau isoform lacking N-terminal sequences (4R0N) and enhanced green fluorescent protein (EGFP) into Neuro-2a cells. EV-mediated transfection efficiency was compared with conventional methods, including lentiviral and chemical (lipofectamine and polyethyleneimine, PEI) approaches. Response surface methodology (RSM) was used to optimize EV-mediated delivery parameters.ResultsEVs successfully delivered large plasmid DNA into Neuro-2a cells, resulting in detectable tau and EGFP expression. Optimization via RSM further improved gene delivery efficiency and reproducibility compared to unoptimized EV preparations and conventional transfection methods.DiscussionThese findings demonstrate that EVs can serve as a robust and biocompatible platform for tau gene delivery, providing a promising alternative to traditional transfection strategies for generating physiologically relevant tauopathy models.